Bibliometric Studies and Public Administration Research Potential on Stunting Problems - Trio Saputra; Sulaiman Zuhdi; Aguswan Aguswan; Reno Affrian; Eka Eka; Wasiah Sufi; Juraida Roito Harahap (Jurnal Manajemen Pelayanan Publik, 2023)
Stunting is an urgent issue that must be addressed immediately because it will affect the quality of Indonesia's human resources in the future. Human resources are the essential factor that determines the success of a country. This research aims to examine the development of stunting research in 2017-2022. Bibliometrics helps communicate discipline developments for other research purposes. This research aims to map the development of stunting research in 2017-2022. The findings of this study can be a starting point for further research on stunting. The research method employed was quasi-qualitative and bibliometric analysis. The research data is from articles from Google Scholar metadata for 2017-2022. The keyword "stunting" for screening articles and journals must be indexed on Google Scholar or SCOPUS. The results of this study indicate that the 994 articles indexed in Google Scholar and SCOPUS are indexed research articles. Trends in public administration research topics include policy implementation, policy evaluation, government, innovation, and community participation and potential for further research related to the study of collaborative governance within the framework of cooperation and effective institutional models for stunting.